BK Channel Gating Mechanisms: Progresses Toward a Better Understanding of Variants Linked Neurological Diseases - Cui, Jianmin (Frontiers in Physiology, 2021)
The large conductance Ca2+-activated potassium (BK) channel is activated by both membrane potential depolarization and intracellular Ca2+ with distinct mechanisms. Neural physiology is sensitive to the function of BK channels, which is shown by the discoveries of neurological disorders that are associated with BK channel mutations. This article reviews the molecular mechanisms of BK channel activation in response to voltage and Ca2+ binding, including the recent progress since the publication of the atomistic structure of the whole BK channel protein, and the neurological disorders associated with BK channel mutations. These results demonstrate the unique mechanisms of BK channel activation and that these mechanisms are important factors in linking BK channel mutations to neurological disorders.